E-CRM IN THE PROCESS OF IMPROVING WEB-BASED SALES SYSTEM AT ZAHREEN'S SHOP - dewi Antika; Fauriatun Helmiah; Wiwin Handoko (Jurnal Teknik Informatika (Jutif), 2022)
A Competition in various industries in Indonesia is getting tougher. Various companies are vying to be at the forefront of consumers' minds. One of the strategies implemented is the Customer Relationship Management (CRM) strategy. Electronic Customer Relationship Management (E-CRM) is part of a business strategy aimed at maintaining customer loyalty and satisfaction. Technological advances encourage companies to make breakthroughs, one of which is combining CRM business strategies with information technology. The purpose of this study is to overcome these problems, namely by building E-CRM combined with information technology, so that it is hoped that it can help monitor the product improvement process that customers complain about and find out what customers need. The problems that occur at Zahreen Store are, the sales process at Zahreen Store is still doing conventional sales, there are no facilities that help customers to get information, convey an assessment of the product and also experience difficulties in processing and storing customer data that has made transactions buy and sell. This study utilizes CRM features that aim to help the service system at Zahreen Store to attract new customers and retain old customers and expand the sales system. The research method used is a qualitative research method by conducting interviews and observations. This application is made using PHP as programming material and MySQL as database server.